2010
DOI: 10.5032/jae.2010.04059
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Supervised Agricultural Experience Programs: The agriculture teachers’ perspective

Abstract: The purpose of this qualitative exploratory study was to examine how agriculture teachers implement supervised agricultural experience (SAE). A combination of focus groups and individual telephone interviews were conducted. Iowa agriculture teachers offered SAE because it is (a) a means of developing life skills, (b) a component of the FFA award system, and (c) theoretically, one-third of the agricultural education model. Although agriculture teachers were able to talk conceptually and theoretically about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 25 publications
2
70
0
Order By: Relevance
“…Novice (preservice) teachers are entering the profession having high self-efficacy toward their perceived abilities to develop, implement, communicate, maintain, sustain, evaluate, and supervise SAE; yet current teachers struggle with many aspects of SAE (Swortzel, 1996). Dyer and Osborne (1995), Retallick (2010), and Wilson and Moore (2007) all indicated that teachers do not implement SAE programs as they are conceptually and theoretically defined. Therefore, a gap between what is taught in pre-service programs and what is implemented in the classroom by practicing teachers exists.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Novice (preservice) teachers are entering the profession having high self-efficacy toward their perceived abilities to develop, implement, communicate, maintain, sustain, evaluate, and supervise SAE; yet current teachers struggle with many aspects of SAE (Swortzel, 1996). Dyer and Osborne (1995), Retallick (2010), and Wilson and Moore (2007) all indicated that teachers do not implement SAE programs as they are conceptually and theoretically defined. Therefore, a gap between what is taught in pre-service programs and what is implemented in the classroom by practicing teachers exists.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Since the mid-1980's, student participation and teacher usage of SAE programs has continued to decrease (Barrick, Hughes, & Baker, 1991;Dyer & Osborne, 1995;Phipps et al, 2008;Retallick, 2010;Roberts & Harlin, 2007;Steele, 1997;Wilson & Moore, 2007). Further, Steele (1997) conjectured that the removal of the federal legislative requirement has affected the utilization of supervised experiences within school-based agricultural education (SBAE) nationwide.…”
mentioning
confidence: 99%
See 3 more Smart Citations